FAKTOR-FAKTOR PENENTU KUALITAS PELAYANAN KESEHATAN –STUDI DI PUSKESMAS KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - KANDOU, RIVANO EDUARD; Mandey, Jantje; Pombengi, Jericho DANGA (Sam Ratulangi University, 2016)
abstract: the clinic is an organization which organizes functional health effort that is comprehensive,integrated, equitable, acceptable and affordable by the community, with the active participation of thecommunity and using the results of the development of science and appropriate technology, with a cost thatcan be borne by the Government and the community.This research is intended to provide a quantitative picture clearly about the problems examinedinterpret and explain the data systematically. The population in this research is a society which is at workareaclinics Talawaan ever sought to seek as much as 200 patients per month, for a year in terms of about800 patients and samples in this study amounted to 89 people respondents.Based on the results of the research showed that the factors that affect the quality of health services clinics inNorth Minahasa Regency Talawaan consists of six factors in accordance with the results of the sixth dataprocessing those factors that affect the Health Ministry Talawaan wellKeywords: quality of service, health